THEORETICAL STUDY OF THE QUALITY INDICATORS OF TWO-LAYER KNITTED FABRICS OF A NEW STRUCTURE BASED ON A MATHEMATICAL MODEL - Khalikov Kurbanali Madaminovich; Ergashev Jamoliddin Samadovich; Kurbanov Bahadir Mamadalievich; Oralov son of Lazizbek Sayibnazar (American Journals Publishing, 2023)
In this article, the quality indicators of two-layer knitted fabrics of a new structure are theoretically studied on the basis of a mathematical model.
Keywords: Textile, industry, mathematical, modeling, volumetric density, ring pitch, air permeability, isoline, inlet, property.